1987
DOI: 10.1097/00006842-198709000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress and immunity in family caregivers of Alzheimerʼs disease victims.

Abstract: Although acute stress has been associated with transient immunosuppression, little is known about the immunologic consequences of chronic stress in humans. In order to investigate possible health-related consequences of a long-term stressor, we obtained blood samples for immunologic and nutritional analyses and psychologic data from 34 family caregivers of Alzheimer's disease (AD) victims and 34 sociodemographically matched comparison subjects. Family caregivers for AD victims were more distressed than compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
191
2
3

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 452 publications
(209 citation statements)
references
References 49 publications
10
191
2
3
Order By: Relevance
“…No significant changes in antibody titers to poliovirus type-2 (a non-latent virus) and no evidence for a primary infection with EBV were observed (I 1). Consistent with these data from medical students, we found higher antibody titers to latent EBV in AD family caregivers than well-matched controls (2,15).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…No significant changes in antibody titers to poliovirus type-2 (a non-latent virus) and no evidence for a primary infection with EBV were observed (I 1). Consistent with these data from medical students, we found higher antibody titers to latent EBV in AD family caregivers than well-matched controls (2,15).…”
Section: Introductionsupporting
confidence: 88%
“…In previous studies involving caregivers of dementia patients, we found evidence of the modulation of latent EBV (2,15). These studies were extended to determine if the virus-specific immune response to latent HSV-1 infection was influenced by the stresses of caregiving with respect to three different markers related to the HSV-1 specific immune response: levels of neutralizing antibody, antibody titers to a total viral antigen preparation, and a memory proliferative T-cell response.…”
Section: Discussionmentioning
confidence: 70%
“…Stone and colleagues [29,30] required participants to swallow a capsule containing rabbit albumin each morning for [8][9][10][11][12] weeks, and then measured the daily specific sIgA response in saliva, as well as daily mood [29] and events [30]. This methodology allowed within-subject comparisons between antibody levels on high-stress and low-stress days.…”
Section: Secretory Iga Responsesmentioning
confidence: 99%
“…People experiencing periods of chronic stress have been shown reductions in the number of helper T-lymphocytes [11][12][13], B-lymphocytes [14], and salivary concentrations of secretory immunoglobulin A (sIgA) [15][16][17][18], compared to controls. The clinical implications of reductions in these cell counts in healthy people, and within normal ranges, are unclear [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation